Uneven human capital development in contemporary China: a non-monetary perspective on regional and gender inequality - Su, Fang (2011)
Regional inequality is one of the most challenging issues facing China in the coming decade. Whilst this matter can be approached from different angles; mainstream scholars have tended to examine this issue by way of monetary measurement (e.g. GDP or income per capita). This study draws attention to the non-monetary aspect in order to shed new light on regional inequality.